Lexical Cohesion Analysis of Muniba Muzari’s “We All Are Perfectly Imperfect” Speech - Hutagaol, Jelly; Mubarak, Zia Hisni (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This study aims to characterize the various forms of lexical cohesion in Muniba Muzari's speech. It's a component of the qualitative descriptive approach. The data for this study were gathered using a non-participatory strategy and an observational approach. Research employed the competence-in-equalizing technique and the identity technique as a technique and method for data analysis. This study employed the (Halliday and Hasan 1976) theory of lexical cohesion. The researcher identifies 5 repetitions, 1 synonym, 5 antonyms, and 4 collocations from opinion and reportage within Muniba Mazari's speech. Based on this study, the researcher may conclude that the more prevalent type of lexical coherence discovered in Muniba Mazari's speech and ideas is repetition. The study's findings demonstrated the existence of six different lexical cohesion categories: collocation, hyponymy, synonymy, antonymy, and repetition. The data of this research were words, phrases, and sentences.